Enhanced Hydrogen and Methane Production from Sewage Sludge by Addition of Cornstalk in Two-Stage Fermentation Process - Liu, Di; Ying Li, Ru; Ji, Min; Ming Cai, Yan (Asian Journal of Chemistry, 2013)
Effects of cornstalk addition on hydrogen and methane production from sewage sludge in the two-stage fermentation process were investigated. Results of batch experiments showed that addition of cornstalk increased hydrogen production rate and hydrogen and methane yield of sewage sludge fermentation. At substrate concentration of 10 g-volatile solid/L and the total solid ratio of 2:1 for cornstalk and sewage sludge, hydrogen and methane yields were 13.4 and 172.6 mL/g-volatile solid, respectively. At the hydrogen production stage in the fermentation of the mixture of cornstalk and sewage sludge, more than 80 % of VFA product was acetate, which showed different VFA profile from hydrogen fermentation of sole cornstalk or sole sewage sludge. In the two-stage fermentation process, most of the energy produced was methane energy and hydrogen energy was only 0.3-2.8 % of the total produced energy. Hydrogen yield, methane yield and total biogas energy increased with the proportion of cornstalk.